Chapter Nogmaals kĳken naar de pĳn van anderen, of: de uitdaging van 'wĳ ' - Plate, Liedeke (Amsterdam University Press, 2023)
This essay takes its point of departure in images of the victims of the 2023 Turkish-Syrian earthquake. It examines their rhetoric, comparing them to those of Alan Kurdi, the Syrian toddler who washed ashore on a Turkish beach in 2015, and contrasting with the narrative techniques employed by two contemporary novels. It combines cultural critique with an inquiry into the role of art as an agent of change to imagine new ways of doing citizenship and promoting social change in times of crisis, in line with Rosemarie Buikema's mission to develop new and multilayered scenarios for change and transnational justice.